Profit Sharing System And Agreement Between Vannamei Shrimp Cultivator (Litopenaeus vannamei) With Investors In Independent Generation Production Cooperative In Teluk Pambang Village, Bantan District, Bengkali Regency - Rita Hulina Saragih; Eni Yulinda; Lamun Bathara (Berkala Perikanan Terubuk, 2023)
This research was conducted on June 2022 in Teluk Pambang Village, Bantan District, Bengkalis Regency. The purpose of this study is a profit sharing system and agreement between cultivators and investors in the cultivation of Vannamei Shrimp (Litopenaeus vannamei) Independent Generation Production Cooperative in Teluk Pambang Village, Bantan District, Bengkalis Regency. The method used in this research is the case study method. Determination of respondents using the census method or saturated sample as many as 11 respondents. The profit sharing system from the profit value is divided into 4 categories, namely 80% Investors amounting to Rp. 919,068,648 Land of 10% for land Rp 114,883,581 then for Cultivators such as technicians and employees get 5% of the profit of Rp 57,441,790 then Managers 5% for Rp 57,441,790. Vannamei Shrimp cultivation business is profitable and feasible to continue.